What does she want from me, anyway? : honest answers to the questions men ask about women - Phillips, Holly Faith (Zondervan Pub. House, 1997)
In What Does She Want from Me, Anyway? Holly Phillips reports on the questions she's heard men asking about the women in their lives. In responding to their questions, she provides them with practical strategies they can use to strengthen and enrich those relationships. With rare insight and compassion, Holly tells poignant stories of real men and women in pain and confusion and shows how we all can move toward understanding and healing. She also shares candidly about her own marriage and how it almost came to an end after dreams dissolved into disillusionment and love turned to anger and despair. We see how God helped break through the barriers in the Phillips' marriage to enable Holly and her husband, Randy, to begin to rebuild and restore their marriage into the remarkably strong, vital, and life-giving relationship it has become for both of them today.